PTU-217 Oesophago-gastroduodenoscopy yield in patients with coeliac disease presenting with iron deficiency anaemia: a re-audit. (28th May 2012) - Khatri, K M; Perryman, K; Enefer, S; Sayegh, M
Abstract : Introduction: In our previous audit it was shown that the majority of patients with iron-deficiency anaemia (IDA) suspected of having coeliac disease (CD) underwent oesophago-gastroduodenoscopy (OGD) and duodenal biopsy as a routine procedure, but only 0.2% patients had serum coeliac screening prior to OGD. It was suggested that routine duodenal biopsy could be avoided by routine serum coeliac screening, as recommended by the British Society of Gastroenterology (BSG). The purpose of this current study was to complete the audit cycle. Methods: Data related to histology and serum coeliac screen of all patients with IDA undergoing OGD in a District General Hospital from January 1st to October 31st 2011 were evaluated. Data were extracted from Gastrointestinal reporting tool ® and analysed in Microsoft Excel ® spreadsheet. Results: A total of 732 patients with IDA were referred for OGD. There were 282 male and 450 female patients with a mean age of 69.1 years. Duodenal biopsy was performed in 610 patients (83.3%) at the time of OGD; CD was confirmed histopathologically in 17 patients (2.8%). Duodenal biopsy was normal in 593 patients (97.2 %). A total of 122 patients (16.7 %) had serum coeliac screening prior to OGD; 7 cases (5.7%) were positive. Conclusion: Completing the audit cycle it was found that the majority (83.3%) of patients with suspected CD presenting with IDA continue to undergo OGD and duodenal biopsy as a routine procedure. CD was confirmed histopathologically in 2.8% of cases (compared with 2.52% previously). Of note, 16.7% of patients had serum coeliac screening prior to OGD, compared with 0.2% previously. While this represents an improvement in practice the need for wider use of coeliac screening appears to remain Competing interests: None declared.